Automatic score in archery target using simple image processing method - Qohar, A.; Akbar, R.; Hendriawan, A. (Proceedings of the 5th International Conference on Applied Science and Technology on Engineering Science (iCAST-ES 2022), 2022)
In this paper we present our developing tool in archery for judging system, which is workable for outdoor and indoor archery competition. The system used in this tool uses a camera to capture archery targets then the frames obtained from the camera will be processed using the opencv library to get the score. We do a test simulation program using opencv and python with video input as an experimental object. We have successfully collected data from 4 subjects with different brightness settings. The results obtained using this system for score detection accuracy is 96.55%. This paper introduces a new judging system with high accuracy and displays the results.